Exosomes and Stem Cells in Degenerative Disease Diagnosis and Therapy - Yu-Hsun Chang; Kung-Chi Wu; Horng-Jyh Harn; Shinn-Zong Lin; Dah-Ching Ding (Cell Transplantation, 2018)
Stroke can cause death and disability, resulting in a huge burden on society. Parkinson’s disease (PD) is a chronic neurodegenerative disorder characterized by motor dysfunction. Osteoarthritis (OA) is a progressive degenerative joint disease characterized by cartilage destruction and osteophyte formation in the joints. Stem cell therapy may provide a biological treatment alternative to traditional pharmacological therapy. Mesenchymal stem cells (MSCs) are preferred because of their differentiation ability and possible derivation from many adult tissues. In addition, the paracrine effects of MSCs play crucial anti-inflammatory and immunosuppressive roles in immune cells. Extracellular vesicles (EVs) are vital mediators of cell-to-cell communication. Exosomes contain various molecules such as microRNA (miRNA), which mediates biological functions through gene regulation. Therefore, exosomes carrying miRNA or other molecules can enhance the therapeutic effects of MSC transplantation. MSC-derived exosomes have been investigated in various animal models representing stroke, PD, and OA. Exosomes are a subtype of EVs. This review article focuses on the mechanism and therapeutic potential of MSC-derived exosomes in stroke, PD, and OA in basic and clinical aspects.